Pengaruh Modal Sendiri Total Piutang Dan Total Hutang Terhadap Kinerja Keuangan Pada Koperasi Citra Hidup Tribuana Kalabahi Kabupaten Alor - Langkaming, Sarlota; Sabu, Junius Menase Sau; Maro, Yustina; Tang, Sefnat Aristarkus (Jurnal Ilmiah Wahana Pendidikan, 2023)
Financial performance is the achievement or result received by the cooperative in carrying out its business operational activities and this study aims to determine the effect of own capital, total receivables and total debt. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This research uses secondary data with population and the sample is financial performance at Citra Hidup Tribuana Kalabahi Cooperative, Alor Regency. The samples in this study are financial reports related to Own Capital, Total Receivables, Total Debt and financial performance reports at Citra Living Tribuana Cooperative Kalabahi Year (2018-2022). The statistical method used in this study is multiple linear regression. The results of this study indicate that: Partially the equity variable has a significant value of 0.023 where this value is smaller than the alpha value of 0.05 so that the results of this study accept H1 which states that partial equity has a positive effect on financial performance at the Living Image Credit Cooperative Tribuana Kalabahi, Alor Regency. Partially, the total receivables variable has a significant value of 0.011, where this value is smaller than the alpha value, which is 0.05, so the results of this study accept H2 which states that the partial total receivables has a positive effect on financial performance at Citra Hidup Tribuana Kalabahi Kopdit, Alor Regency. Partially the total debt variable has a significant value of 0.000 where this value is smaller than the alpha value, which is 0.05 or 5% so that the results of this study accept H3 which states that total debt partially has a positive effect on financial performance at the Image Credit Cooperative of Tribuana Kalabahi District Alor. Simultaneously the variable equity, total receivables and total debt has a significant value of 0.000 where this value is smaller than the alpha value, namely H4 which states that equity, total receivables and total debt simultaneously have a positive effect on financial performance at the Citra Living Cooperative Tribuana Kalabahi Alor Regency.